Role of Special School Violence Prevention and Handling Team in Bullying Prevention - Amani, Risca; Nofalia, Pina; Yusrawati, Yusrawati; Sumarni, Titin; Rahmahtrisilvia, Rahmahtrisilvia; Z, Martias; Nurhastuti, Nurhastuti (Proceeding of International Conference on Special Education in South East Asia Region, 2024)
Bullying is a serious problem that can occur in a variety of environments, including Special Schools. Children with special needs are vulnerable to becoming victims of bullying. If not prevented and handled properly, it has a negative impact on the physical, mental, and academic achievement of children. The purpose of this study is to describe the role of violence prevention and handling teams in Special Schools in overcoming bullying. The method used in research is qualitative descriptive. The sample in this study was Special School teachers spread across the West Sumatra region. The data collection techniques used are observation, interviews, and documentation. Data is analyzed interactively by reducing data, displaying, and drawing conclusions. The results of this study show that the existence of a Violence Prevention and Handling Team plays an important role in handling bullying cases that occur in Special Schools